PENGARUH MODEL PEMBELAJARAN BLENDED LEARNING TERHADAP HASIL BELAJAR MAHASISWA DI PERGURUAN TINGGI - HILALLUDIN HILALLUDIN; ABDI HARIAWAN AKBAR (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2026)
The development of information and communication technology (ICT) has revolutionized the world of education, driving the transformation of learning systems from conventional models toward more flexible and adaptive approaches. In the context of the Industrial Revolution 4.0 and Society 5.0, higher education is required not only to pursue technological innovation but also to uphold humanistic values. One rapidly evolving approach is blended learning—a model that combines online and face-to-face learning methods. This approach is considered effective in enhancing flexibility, active participation, and student learning independence. However, the implementation of blended learning in Indonesia remains suboptimal due to various challenges, including limited infrastructure, low digital literacy, and insufficient pedagogical readiness among lecturers. This study employs a qualitative approach through a literature review to analyze the impact of blended learning on student learning outcomes, covering cognitive, affective, and psychomotor aspects. The findings indicate that blended learning has significant potential to improve learning outcomes, especially when supported by appropriate instructional design and adequate infrastructure. Nevertheless, the successful implementation of this model largely depends on strong institutional support, faculty training, and equitable access to technology. Therefore, blended learning should be seen not merely as a technical innovation but as a strategic transformation toward a more inclusive, effective, and sustainable higher education system in the digital era.